The Effect of Influential Factors of Knowledge Sharing on Human Resources Development and the Modifying Role of Soft Skills: A Survey Study of a Number of Faculty Members’ Opinions in Some Iraqi Public Universities - Ghanim Al-Bayati , Bashar; Abdullah Al-Shalma , Maysoon (Jordan Journal of Business Administration, 2025)
The aim of this study is to describe the effect of influential factors of knowledge sharing on developing human resources and to describe the modifying role of soft skills of faculty members and their effect on modifying the relationship between the influential factors of knowledge sharing and human resources development in some Iraqi universities. To achieve these aims, the quantitative approach was adopted. Data was collected by using Google questionnaire form, which was designed to gather data via the Internet from the selected research sample, which consists of faculty members of four Iraqi public universities, viz. University of Mosul, University of Tikrit, University of Kirkuk, and University of Zakho. For data analysis, (SPSS26) computer software program was employed, and the Structural Equation Modeling (AMOS24) was used to extract the results. The results of the research showed that there is an effect of knowledge sharing factors on human resources development (HRD) in the investigated universities. After incorporating soft skills completely to modify the relationship, the effect turned out to be stronger; i.e., soft skills positively and directly modified the effect between (KS) and (HRD). However, when soft skills were investigated separately, the effect was positive and significant only for leadership skill, while other skills; i.e., communication, critical thinking, teamwork, and cooperation, had weak effects, and the relationship was negative. The research contributes to providing quantitative research to enhance academic literature through the results reached; as it addressed the influential factors of knowledge sharing and the role of soft skills to modify the relationship between (KS) and (HRD). It is a unique research that has not been conducted before by any other researchers.